Sairaudet ja loukkaantumiset jalkapallon naisten pääsarjatasolla Suomessa - Tulla, Lauri (2025)
Tulla, L. 2025. ILLNESSES AND INJURIES IN TOP-LEVEL WOMEN'S FOOTBALL IN FINLAND. University of Jyväskylä, Master’s thesis, 52 pp., 3 appendices.